Kedudukan Perkawinan Campuran Tanpa Perjanjian Kawin Atas Jual Beli Apartemen Dengan Hak Guna Bangunan - Raihana Anjani, Callista; Yuliana Nualedang , Victoria (Dinasti Research, 2025)
This research aims to examine marriages between Indonesian citizens and foreigners, known as mixed marriages, mixed marriages, namely marriages between citizens based on various kinds of differences, one of which is differences in nationality. The legal consequences of this marriage concern the assets obtained during the marriage. If you do not previously make a marriage agreement containing arrangements regarding assets, then the assets acquired during the marriage are considered joint assets. A property separation agreement can be made at the time of marriage, before the marriage takes place, or during the marriage. Then, based on the provisions of Article 21 of Law Number 5 of 1960 concerning Basic Agrarian Principles Regulations, Indonesian citizens who carry out mixed marriages can have the same rights to land as other Indonesian citizens who do not carry out mixed marriages, but this must be proven by a property separation agreement. Husband and wife have the right to manage joint property with the consent of both parties. One of the actions that requires the consent of the parties regarding joint property is the act of selling and buying something, one of which is buying property to be used as a residence, so an agreement between the parties is needed to determine ownership rights. The existence of mixed marriages without a marriage agreement gives rise to legal consequences related to the status of ownership rights to land.